Humoral immune response and spreading of Encephalitozoon cuniculi infection in experimentally infected ponies - Wagnerová, Pavla; Sak, Bohumil; Květoňová, Dana; Maršálek, Miroslav; Langrová, Iva; Kváč, Martin (Veterinary parasitology, 2013)
A total of 9 (8 stallions and 1 mare) 1 year old ponies were used for the experimental infection caused by Encephalitozoon cuniculi genotype II (10(7) spores per animal). Subsequently, individual horses were slaughtered 7, 14, 21, 28, 35, 42, 49, 56, and 63 days post infection. Immediately after slaughter, tissues samples of stomach, duodenum, jejunum, ileum, caecum, colon, spleen, liver, kidney, bladder, heart, lungs, and brain were sampled. In addition, urine, feces and blood specimens were collected. Enzyme-linked immunosorbent assay was used for determination of humoral immune response and nested PCR targeting 16S rDNA, whole ITS, and 5.8S rDNA was used for detection of E. cuniculi in collected organs, blood, feces and urine. No clinical signs of microsporidiosis including diarrhea or colic, neurological signs and fever were observed in any horses during whole experiment. Acute microsporidiosis in ponies was characterized by the dissemination of microsporidia into almost all organs and significant increase of concentration of specific antibodies in blood was observed from 28 to 42 DPI. After this acute stage microsporidia disappeared from most organs with the exception of the kidney, which was positive up to 63 DPI when the experiment was terminated. No pathological changes were observed in any organs with exception of one mare's brain, where E. cuniculi-positive cavity measuring 5 cm × 3 cm in diameter formed in the lobus piriformis.
Keywords: koně; Encephalitozoon cuniculi; Immunity, Humoral; Female; Animals; Male; Horse Diseases; Horses; nemoci koní; zvířata; mužské pohlaví; humorální imunita; Encephalitozoonosis; ženské pohlaví; encephalitozoonóza